Perancangan Sıstem Informası Penjualan dı Unıon Jaya - Muhammad Ardiansyah; Jukenly Jukenly (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
The current modern era is an era that is very dependent on network and internet, one of the benefits is to provide convenience, especially for MSMEs ( Micro, Small, and Medium EnterPrises), Company located behind padang called Union Jaya is one of them, they still use book to record all their transactions so that the data is invalid and cannot be used as a reference for store development. So this practical work aims to help Union Jaya companies to manage data, cash register systems, and valid report, this website is designed using a PHP program and then impelemented according to the company’s criteria, this website is expected to be able to ease the owner’s handle the store and provide references, especially when owner taking business decisions for the future and can be a solution for other PkM.